A CD63 Homolog Specially Recruited to the Fungi-Contained Phagosomes Is Involved in the Cellular Immune Response of Oyster Crassostrea gigas - Liu, Conghui; Yang, Chuanyan; Wang, Mengqiang; Jiang, Shuai; Yi, Qilin; Wang, Weilin; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2020)
Cluster of differentiation 63 (CD63), a four-transmembrane glycoprotein in the subfamily of tetraspanin, has been widely recognized as a gateway from the infection of foreign invaders to the immune defense of hosts. Its role in Pacific oyster Crassostrea gigas is however yet to be discovered. This work makes contributions by identifying CgCD63H, a CD63 homologue with four transmembrane domains and one conservative CCG motif, and establishing its role as a receptor which participates in immune recognition and hemocyte phagocytosis. The presence of CgCD63H mRNA in hepatopancreas, labial palps, gill and hemocytes is confirmed. The expression level of mRNA in hemocytes is found significantly (p < 0.01) up-regulated after the injection of Vibrio splendidus. CgCD63H protein, typically distributed over the plasma membrane of oyster hemocytes, is recruited to the Yarrowia lipolytica-containing phagosomes after the stimulation of Y. lipolytica. The recombinant CgCD63H protein expresses binding capacity to glucan (GLU), peptidoglycan (PGN) and lipopolysaccharide (LPS) in the presence of lyophilized hemolymph. The phagocytic rate of hemocytes towards V. splendidus and Y. lipolytica is significantly inhibited (p < 0.01) after incubation with anti-CgCD63H antibody. Our work further suggests that CgCD63H functions as a receptor involved in the immune recognition and hemocyte phagocytosis against invading pathogen, which can be a marker candidate for the hemocyte typing in C. gigas.